Hubungan Intensitas Kebisingan Dan Beban Kerja Dengan Stres Kerja Pada Pekerja Bagian Spinning Di PT. Kusumaputra Santosa Karangayar - Prasetia, Hafidh Agung Dwi; , H. Heru Subaris K, SKM, M (2016)
The Sound from spinning engine at textile mill above threshold 85 db could cause noise. Engine noise could cause disorder of workers like job stress. Close with spinning machine can increase workload and increasing pulse. The purpose of this study is to know correlationnoise intensity and workload with job stresson part of spinning workers in KusumaputraSantosa corporation of Karangayar. The method use analytic observational with cross sectional approach. The sample was all of workers of spinning part count 59 persons, with taking sample use total of sampling. Research instruments use noise measurement, pulse measurement and stress questionnaires. analysis data use correlation Pearson product moment and rank spearman test.The results showed that average noise intensity was 90.91dB. There were 14 respondents with workload medium category and 29 respondents with workload light category. There were 27 respondents with medium stress category, 19 stress light category, 13 respondents with no stress. Correlation intensity noise with stress Test obtained p= 0,001. Correlation workload with stress test obtained p= 0,001. conclusionof this research, there is correlation noise intensity and workload with job stressof spinning workers in Kusumaputrasantosa corporation of Karangayar.